Designing a paediatric hospital information tool with children, parents, and healthcare staff: a UX study - Lisa Aufegger; Khánh Hà Bùi; Colin Bicknell; Ara Darzi (BMC, 2020)
Abstract Background The hospital patient pathway for having treatment procedures can be daunting for younger patients and their family members, especially when they are about to undergo a complex intervention. Opportunities to mentally prepare young patients for their hospital treatments, e.g. for surgical procedures, include tools such as therapeutic clowns, medical dolls, or books and board games. However, while promising in reducing pre-operative anxiety and negative behaviours, they may be resource intensive, costly, and not always readily available. In this study, we co-designed a digital hospital information system with children, parents and clinicians, in order to prepare children undergoing medical treatment. Method The study took place in the UK and consisted of two parts: In part 1, we purposively sampled 37 participants (n=22 parents, and n=15 clinicians) to understand perceptions and concerns of an hospital information platform specifically design for and addressed to children. In part 2, 14 children and 11 parents attended an audio and video recorded co-design workshop alongside a graphic designer and the research team to have their ideas explored and reflected on for the design of such information technology. Consequently, we used collected data to conduct thematic analysis and narrative synthesis. Results Findings from the survey were categorised into four themes: (1) the prospect of a hospital information system (parents' inputs); (2) content-specific information needed for the information system (parents' and clinicians' inputs); (3) using the virtual information system to connect young patients and parents (parents' inputs); and (4) how to use the virtual hospital information system from a clinician's perspective (clinicians' inputs). In contrast, the workshop highlighted points in times children were most distressed/relaxed, and derived the ideal hospital visit in both their and their parents' perspectives. Conclusions The findings support the use of virtual information systems for children, in particular to explore and learn about the hospital, its facilities, and the responsibilities of healthcare professionals. Our findings call for further investigations and experiments in developing safer and more adequate delivery of care for specific age groups of healthcare users. Practical and theoretical implications for improving the quality and safety in healthcare delivery are discussed.